Creative Play Based on Task Stimulation and Early Childhood Development - Hendi Dewantara; Dwi Fahira Utari (Universitas Negeri Padang, 2019)
The world of early childhood is a world of play, a portion of children's lives are spent with play activities. play is a condition that makes a pleasant and spontaneous atmosphere that gives a sense of security to the psychology of early childhood. During active play also shapes the atmosphere of the child exploring his curiosity so that the child is free to express according to the ideas he has. In psychology that describes a sense of security and freedom is a crucial condition that supports the growth of creativity.Keywords: Creative Play, Stimulation, Developmental Tasks, Early Childhood